2013
DOI: 10.1007/s00449-013-0998-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of dielectric spectroscopy for monitoring high cell density in monoclonal antibody producing CHO cell cultivations

Abstract: The application of dielectric spectroscopy was frequently investigated as an on-line cell culture monitoring tool; however, it still requires supportive data and experience in order to become a robust technique. In this study, dielectric spectroscopy was used to predict viable cell density (VCD) at industrially relevant high levels in concentrated fed-batch culture of Chinese hamster ovary cells producing a monoclonal antibody for pharmaceutical purposes. For on-line dielectric spectroscopy measurements, capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Especially during the model validations with the test set, the three multivariate regression models showed a remarkable reduction in prediction errors, which ranged from a 64 to 79% improvement over that of the simple Cole‐Cole approach. This is generally in agreement with previous studies …”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Especially during the model validations with the test set, the three multivariate regression models showed a remarkable reduction in prediction errors, which ranged from a 64 to 79% improvement over that of the simple Cole‐Cole approach. This is generally in agreement with previous studies …”
Section: Resultssupporting
confidence: 94%
“…LWPLS) in their functional form. These features are what allow us to differentiate our study from those of others . The first three batches (B1, B2 and B3) were used as a calibration set to build the regression model, and the remaining two batches (B4 and B5) were utilized as a test set to validate the prediction power of the constructed models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At low volume fractions non-biological solid particles or dead cells, with permeable membrane, do not interfere with the dielectric signal [18]. It has been successfully shown that suspension cultures can be monitored on-line using single frequency measurements [19,20] or frequency scans [16,17] in stirred tank reactors.…”
Section: Successful Applicationsmentioning
confidence: 99%